Prevalence of polypharmacy and its associated factors: a cross-sectional study among elderly population - Sastry, Nidhi P.; Deshmukh, Jyotsna S. (International Journal of Research in Medical Sciences, 2025)
Background: Polypharmacy is the concurrent use of multiple medications, defined as the routine use of five or more medications. With such a dynamically growing elderly population, concerns regarding polypharmacy and its effect on this geriatric population need to be studied. Hence, this study aims to estimate the prevalence of polypharmacy among elderly and its associated factors and impact. Methods: A cross-sectional study was conducted in the outpatient department (OPD) of an Urban Health Training Centre affiliated to a tertiary health care hospital in Maharashtra among 150 elderly patients above 60 years of age. Association between polypharmacy and study variables were assessed using Chi-square test. Results: Mean age of participants was 69.23±5.90 years. Prevalence of polypharmacy in our study was 76 (50.67%). It was observed that maximum patients 48 (32%) took 5 medicines and hypertension was the most common morbidity 68 (45.33%). Conclusions: The associated factors with polypharmacy were found to be age, education, socioeconomic status, number of morbidities, number of doctors consulted, hospital admission in the last 3 months. The impact of polypharmacy on adverse drug reactions, out of pocket expenditures and adherence to medications were found to be significant.